Know the Names of the Angels and Their Duty with Media Puzzle (Global Scientific Review, 2022)
Puzzles are form the game in it there is activity unpack and assemble return pieces or picture Becomes form complete picture. Activity our project ie about “Knowing the Names of Angels Together With The task With Using Media Puzzles”. As for goals from making project with using the media Puzzle is for practice spikomotor children participant educate school basic. Children age school base also earn supplies with related education about religious, yes increase aspect development physique cognitive and attitude high religious. In Settings atmosphere in class our must arrange in a manner comfortable and fun, the participants educate could with free express and create at the same time match the puzzle accordingly with place that has been set.